Novel safety evaluation technique for ships in offshore anchorage under rough seas conditions for optimal ship routing. (1st June 2022) - Lee, Sang-Won; Sasa, Kenji; Chen, Chen; Waskito, Kurniawan T.; Cho, Ik-Soon
Abstract: In recent years, the number of waiting ships in offshore anchorage has increased owing to several reasons, such as the port lockdown and increased cargo volumes in maritime transportations. Moreover, port terminals have ordered ships to stay outside the harbor to prevent mooring accidents when rough waves are forecasted. Anchored ships have been exposed to dangers owing to dragging anchors under rough sea conditions, especially those facing the open seas. In this study, we perform a numerical simulation of anchored ship motions to reproduce the dragging anchor. Additionally, we further evaluated the anchored ship motions based on underestimated wave conditions. Lastly, we constructed a novel risk assessment technique for anchored ships to assess the stranding risk, damage to marine structures, and risk of collision. The stranding risk was evaluated based on the relationship between the vertical displacement and Under Keel Clearance (UKC). Damaging risk can be identified from the information of harbor charts. The risk of collision was quantitatively assessed considering the main influential factors such as Closest Point of Approach (CPA), and the Ship Domain Overlapping Index (SDOI). Results showed that the proposed methodology can contribute to port safety and ship operation in terms of optimal ship routing. Highlights: Anchored ship motions are simulated for 28, 000-DWT bulk carrier. Drifted distance of anchored ship can be estimated with underestimated waves. Risk of stranding is assessed by the UKC and vertical displacements. Risk of collision can be quantitatively estimated with relative ship's positions.